Spearcons for Patient Monitoring: Program of Laboratory-Based Feasibility Studies. (November 2019) - Li, Simon Y. W.; Yeung, Chun-Wan; Davidson, Thomas; Ryu, Younji; Srbinovska, Monika; Salisbury, Isaac; Loeb, Robert G.; Sanderson, Penelope M.
Clinicians are not always at their patients' bedsides and may therefore need ways of remotely monitoring the well-being of multiple patients under their care. We outline the main findings of a research program investigating whether the intermittent presentation of short phrases of time-compressed speech (spearcons) is an effective way of giving mobile clinicians information about their patients without annoying either clinician or patient. We provide a high-level overview of several studies investigating participants' ability to understand spearcons, both individually and in sequences representing multiple patients. We then report in more detail a recent small study testing whether participants' ability to understand spearcons is compromised by different kinds of ongoing tasks. Finally, we outline further issues that should be addressed and further research studies performed before spearcons could be considered a viable tool for patient monitoring.